Integration of Islamic Education in the Sustainable Development Goals Approach (SDGs) - Septi Megasari; Burniat Burniat; Hilmin Hilmin; Dwi Noviani (World Journal of Islamic Learning and Teaching, 2025)
Islamic education plays a strategic role in supporting the achievement of the Sustainable Development Goals (SDGs), particularly in the areas of social empowerment and environmental preservation. This research is motivated by the need for an educational approach that is not only religious but also capable of driving fair and sustainable social transformation. This study aims to analyze how Islamic education, especially through institutions such as Islamic boarding schools and madrasas, integrates sustainability values into curricula and daily practices. The method employed is qualitative research with a descriptive-analytical approach, examining various Islamic educational practices that align with the principles of the SDGs. The results show that Islamic values such as maslahah 'ammah (public benefit), justice, and the role of humans as khalifah (stewards) strongly support the foundations of sustainable development. Islamic educational institutions have been actively engaged in social, economic, and environmental activities, including skills training, Islamic entrepreneurship, reforestation programs, and waste management. Although challenges remain—such as limited resources and teacher training—Islamic education holds great potential to foster self-reliant and environmentally conscious communities. Through curriculum strengthening, continuous teacher development, and cross-sector collaboration, Islamic education can serve as a powerful driver of change toward a more just and sustainable future.